Spatially arranged chains of Ge quantum dots grown on Si substrate prepatterned by ion‐beam‐assisted nanoimprint lithography. Issue 10 (7th September 2016) - Dvurechenskii, Anatoly; Smagina, Zhanna; Novikov, Pavel; Zinovyev, Vladimir; Kuchinskaya, Polina; Rudin, Sergey; Nenashev, Alexey
Abstract: Joint experimental and theoretical study of Ge nanoislands growth on groove‐patterned Si(001) substrate prepared by ion‐beam‐assisted nanoimprint lithography is carried out. Prepatterning procedure includes ion irradiation of Si substrate through imprinted resist mask with linear mounds and subsequent multistep oxidation/etching of irradiated Si domains. It is shown that the temperature of subsequent heteroepitaxy on the groovepatterned substrate affects the location of Ge nanoislands. The effect is attributed to additional surface tensile strain formed inside grooves by residual irradiationinduced defects. The interplay of strain and surface curvature makes the critical size of 3D nanoisland larger at the concave regions in grooves than between them. At lower temperatures this results in nanoisland nucleation at the top of mounds. At higher temperatures due to the intensive migration of Ge inside grooves the formation of large nanoislands in grooves occurs. The effect of temperature on the location and size of nanoislands is described by Monte Carlo simulations. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)